Web Learning for Pharmacology Courses - Mashuri YUSUF (RADINKA JAYA UTAMA PUBLISHER, 2023)
The learning and teaching process that uses web-based learning media for distance education must be independent and responsible for the learning process. Web-based learning media can learn anywhere, anytime, as long as the tools are available. The research objective was to analyze web-based learning media for distance education. This study uses a systematic literature review method using Preferred Reporting Items for Systematic Review (PRISMA). The research objective was to identify web-based biology learning media for distance education. The results of the study show that through web-based learning media, students can search for and retrieve information or learning materials based on the syllabus or criteria set by the teacher or education manager. Learners will have a wealth of information and can access information from anywhere related to their learning material. Web-based Biology learning media used for distance education can be improved by using well-designed, professional, attention-grabbing learning materials.